Empirical research on corporate strategies in Hungarian dairy industry - Szabó-Szentgróti, Eszter; Szabó-Szentgróti, Gábor; Szakály, Zoltán (Applied Studies in Agribusiness and Commerce, 2017)
Corporate strategy has never been as important as it is nowadays. Markets are changing rapidly because of consumer demands, innovations, information flow and economic changes. Our paper concentrates on Hungarian dairy industry (hereinafter dairy) and four main objectives were defined to be analysed: (1) domestic dairy company features, (2) main strategic characteristics, (3) how companies’ strategy resonates on the consumer side and (4) companies’ financial background were analysed as well. A company database was made in order to prepare for the primary research and to understand better the nature of today’s market. B2B (26 companies) and B2C (503 people) surveys were used in order to gain primary data. In 2017 132 Hungarian companies were observed in milk processing, but 44% of the market participants are not present in dairy competition. It is a fairly fragmented market structure because 10-20% of the annual turnover is accumulated among the 80-90% of competitors. The factor analysis of the data proved that the dairy companies followed m strategies at the same time; and it is assumed that most of them are unconscious. Strategically, the majority of the dairy sector is not up-to-date and modern enough. SMEs sector management skills and strategic preparedness are considered to be out-of-date and insufficient. Strategic planning can possibly have an influence on financial results, which was only partly proved by the analysed criteria system. The production and use of own raw milk supplies might make companies experience financial benefits. Nearly 78% of the respondents would rather purchase goods made from own raw material. The willingness to pay a higher price for this was in average 5-15%. JEL Code: L1, L66